Evaluation and Proposal Repair Safety Culture Maturity Use Safety Model Canvas in Manufacturing Companies - Ardiansyah, Yuda; Tranggono, Tranggono; Sari, Rizqi Novita (Newinera Publisher, 2024)
PT. Rajawali Sumber Rejeki is one of the manufacturing companies that produces cigarettes in Indonesia. The cigarette production process involving large machines has a high potential risk of accidents for employees. This study assesses and proposes improvements to the company's safety culture maturity as a material for evaluating the company's K3 policy so that the number of work accidents in the production process can be minimized. The safety culture maturity assessment involves safety culture variables, namely commitment, leadership, responsibility, competence, engagement & involvement, information & communication, risk, and organizational learning. Data collection was carried out by distributing questionnaires to 60 employees working in the company. Three expert judgments were also involved as determinants of the weight of the safety culture maturity variable using the AHP (Analytical Hierarchy Process) method. In addition, fuzzy theory is also used to reduce the subjectivity of the company's safety culture maturity assessment results. Then the improvement proposal is given with a safety model canvassing based on the results of the safety culture maturity assessment. The results of the study showed that the safety culture maturity of PT. Rajawali Sumber Rejeki is 3.5 which is included in the Complaint level. Based on the safety canvassing model that has been created, the priority for improving the safety culture maturity variables from the first to the last is organizational learning, competence, commitment, information & communication, risk, engagement & involvement, responsibility, and finally the leadership variable.